Public-Private Partnership (PPP) in managing arts, cultural and tourism sector / Qistina Donna Lee Abdullah, Salmiah Abdul Hamid - Abdullah, Qistina Donna Lee; Abdul Hamid, Salmiah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
Public-Private Partnership (PPP) is an increasingly popular choice for policymakers in implementing important public works or events projects especially when facing shortage of government’s financial resources and when it is necessary to counter public inefficiency. Under the Ninth Malaysia Plan, the government had officially announced the implementation of public events using the Public Private Partnership (PPP). The Malaysian Ministry of Tourism and Culture applies this policy whereby they recognize the importance of PPP in sustaining and developing the cultural and tourism industry as the main product in promoting Malaysia to the world. By recognizing these benefits, this evaluative study aims to analyze the effectiveness of the strategic alliances in arts, tourism and cultural organizations based on the Partnership Model adopted from the Government-Non-profit framework. To carry forward this study, quantitative method was employed through survey and questionnaires targeted to the management staffs of selected government agencies, offices, units and private sectors that are engaged in this PPP projects. The data gathered were analyzed through correlation and non-parametric statistics analysis. The final outcome of the survey based on the dimensions constructed in the framework will be implemented in the real PPP collaboration projects.